Parametric analysis for designing low voltage and low frequency energy harvester booster - Che Mustapha, Nurul Arfah; Alam, A. H. M. Zahirul; Khan, Sheroz; Azman, Amelia Wong (2013)
This work presents an ultra-low voltage DC-DC boost converter vibration-based energy harvesting. A switching gate controlled concept is used which is well suited for low vibration-based frequency and voltage applications. The 0.1 – 0.5 V input voltage range is linearly increased with the increase of output voltage range, 4 – 22 V. The transient analysis is simulated to verify the optimum value of the inductive resistance, switching rise and fall times circuit under test. The 10 kΩ load circuit is using 160 μH inductor and 10 μF load capacitor. This voltage converter is suitable for energy harvesting applications in automotive, buried electronic devices for broadband frequency range from 1 kHz to 10 kHz.